Conservation of Traditional Games as Wisdom Value Local and Educational Tourism Attraction - Andari, Rini; Ismarizal, Beni (E-Journal of Tourism; Volume 10 Number 1 (March 2023), 2023)
Rapid technological development not only has a positive effect on education, the negative impact is given such as lack of movement even in a game on the device. Traditional games that are almost extinct can be preserved for preservation as well as an attraction in educational tourism. The purpose of the study was to understand that the conservation of traditional games as a value of local wisdom can be an educational tourist attraction. This research uses qualitative to uncover the meaning of research results with case study techniques. The results of exploration of traditional game conservation in Kampung Adat Banceuy can be beneficial for education, destinations, and also local culture. Educational tourism not only provides benefits for researchers, but for tourists where recreation can be done while learning directly. Keywords: Educational Tourism, Traditional Games, Wisdom Local Value